YAP1 Immunoexpression as a Biomarker of Histological Grade, Lymph Node Metastasis, and Lymphovascular Invasion in Invasive Breast Carcinoma - Redjeb, Yulianti; Nelwan, Berti Julian; Cangara, Muhammad Husni; Miskad, Upik Andriani; Achmad, Djumadi; Yamin, Amalia; Tawali, Suryani (Asian Pacific Journal of Cancer Biology, 2025)
Objective: This research seeks to assess the relationship between YAP1 expression and histological grading, lymphovascular invasion, and lymph node metastasis in patients with invasive breast cancer in Makassar, a study that has not been previously performed. Methods: A cross-sectional study was carried out on 100 mastectomy samples identified as invasive breast carcinoma at Dr. Wahidin Sudirohosodo Hospital, Makassar, Indonesia. YAP1 expression was assessed through immunohistochemistry and scored according to the immunoreactive score (IRS) method. A statistical evaluation was conducted using Fisher’s exact test. Result: The average age of patients was 50.22 ± 10.20 years. YAP1 expression was positive in every instance, with 72% showing strong expression (+3), 25% exhibiting moderate expression (+2), and 3% demonstrating weak expression (+1). A significant correlation existed between YAP1 expression and histological grade (p=0.001), showing increased expression in grade 3 tumors. Nonetheless, no significant correlation was discovered between YAP1 expression and lymph node metastasis (p=0.912) or lymphovascular invasion (p=0.276). Conclusion: YAP1 expression shows a strong correlation with histological grade in invasive breast cancer, indicating its potential as a biomarker for tumor aggressiveness. Nonetheless, YAP1 expression is not directly linked to lymph node metastasis or lymphovascular invasion.